Analysis of Psychosocial Factors Affecting Risky Sexual Behavior in Adolescents - Arfian; Rina Dwi Rahmawati; Nabila Apsarini Ardina Azalia; Hanna Putri Haryanto; Shinta Rizki Febriana (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Background : Sexual behavior in adolescents is a form of sexual exploration that arises from sexual desire, whether carried out individually, with the opposite sex or in relationships with the same sex. These forms of behavior vary, including feelings of interest, flirting to involvement in sex. Sexual behavior in adolescents shows that there is a risk of contracting sexually transmitted diseases if sexual activity continues and leads to worse consequences. Purpose : The purpose of this study is to examine social psychological factors that affect risky sexual behavior and the transmission of sexually transmitted diseases in adolescents. Design/methods/approach : This research data is collected by the literature study method or also known as library research, which is a method that involves collecting data by obtaining understanding and knowledge through theories derived from various literature and previous research results that are relevant to the research topic. Research data is collected by searching for various sources of literature such as books, scientific journals and previous research that has been carried out. Findings : The results of the study showed that knowledge factors, information media, the role of parents and peers had an influence on the formation of sexual behavior in adolescents. Research implications/limitations: Teens who engage in sexual activity are more likely to experience the dangers of STIs, unplanned pregnancies, and sexual anxiety. Additionally, adolescents' mental and emotional health can benefit from sexual involvement, including higher self-esteem and confidence. Originality/value : The conclusion of this study provides a comprehensive overview of the complexity of psychosocial factors that affect adolescent sexual behavior and their implications for the transmission of Sexually Transmitted Infections